Hematocrits of triathletes: is monitoring useful? - O'Toole, M. L.; Douglas, P. S.; Hiller, W. D.; Laird, R. H. (Medicine & Science in Sports & Exercise, 1999)
The purpose of this manuscript was to provide a basis for establishing safety cutoffs for hematocrit levels in triathletes and background data for possible future medical control regulations. Result: Cutoff values (3 SD above the means) of 52% for men and 48% for women are suggested by these data. However, the relationship of these cutoffs to either athlete safety or the ability to detect rules violations remains unknown.